(untitled) (Historia, 2024)
This article takes a rather unorthodox approach for a presidential address at an academic conference. It looks beyond the windows of the ivory tower to take cognisance of what lies outside the walls of academia to engage with what is really happening and what really matters. It is indeed a case of pushing the envelope – going beyond the limits of what is regarded as the norm and acceptable – and in so doing suggests ways in which we can manoeuvre our discipline to consider embracing a different approach regarding where we are at. While historical research is at the core of what we do and is in effect what keeps our academic institutions afloat, it cannot and must not be an end in itself. What I argue for is that we take account of the situation we find ourselves in in terms of our South African university community and by that, I mean our student cohort, and reflect upon what it is we can and need to do. The article reflects on the downturns, considers the wrong directions and proposes additional avenues.